The risks of using unregulated naturopathics to treat psychiatric symptoms - Parikh, Parinda; Gellert, Zoe; Buddhavarapu, Mahiya; Manepalli, Sahia; Shukla, Arnesh; Bhatta, Aatish D.; Singh, Shaurya K.; Pansuriya, Parthiv; Suthar, Himani J.; Chandra, Arushi K.; Oza , Mina (International Journal Of Community Medicine And Public Health, 2025)
Aconitine, a di-terpenoid alkaloid derived from Aconitum species, has been used in traditional Chinese medicine for over 2000 years, yet it’s extremely narrow therapeutic window and potent neurotoxicity and cardiotoxicity make unregulated preparations hazardous. A 30-year-old woman developed acute auditory and visual hallucinations, insomnia, and self-neglect after eight weeks of nightly sublingual use of an over-the-counter “natural” spray labelled as 200 CH Aconitum napellus. Emergency management included long-acting injectable aripiprazole (720 mg), oral olanzapine (5 mg), and clonazepam (5 mg). Three days later, the patient’s psychosis had subsided, although fatigue and weakness persisted. She received a second aripiprazole LAI (675 mg) plus scheduled olanzapine and clonazepam. Analysis of the spray revealed aconitine, implicating substance-induced psychotic disorder (SIPD). Differentiating SIPD from primary psychosis with substance abuse is critical because definitive management relies on prompt removal of the offending agent and antipsychotic therapy. The case highlights how dilution and “natural” labelling can mask the presence of lethal alkaloids, exposing patients to severe neuropsychiatric and cardiovascular events. Even highly diluted aconite remedies can precipitate first-episode psychosis and other life-threatening toxicities. Clinicians should systematically screen for complementary and alternative medicines, educate patients about unregulated products, and advocate for stricter oversight of naturopathic preparations. Public health efforts to pair evidence-based guidance with culturally sensitive counseling are essential to prevent avoidable morbidity and mortality from herbal remedies.